Plastid structure: development and differentiation - Pyke, Kevin (Henry Stewart Talks, 2007)
Plastid structure, Proplastid development and differentiation, Different types of differentiated plastids, Plastid division, Control of plastid morphology
Reviewed at 2020/07/10